CZESŁAW MILOSZ AND TOMAS VENCLOVA’S DISCUSSION ON THE PAST: TRADITION AS THE FOUNDATION OF NATIONAL BELONGING AND SOLIDARITY - Narušienė, Vaiva (Porównania, 2012)
A public discussion between the poets Czesław Miłosz and Tomas Venclova, initiated by the article “Dialogue about Vilnius“ in the Paris-based cultural journal in 1979 and continued for about a quarter of a century, plays a special role in the history of post-war Polish and Lithuanian relations. At those times when Polish and Lithuanian emigrants had unsuccessfully been trying to solve the most relevant issues for decades, these poets gave an example of a constructive dialogue. When addressing the most important and arguable issues associated with the Polish and Lithuanian relations, Miłosz and Venclova looked at the common history and tradition of both nations in order to identify the reasons of their disagreement that often stems from distant past. They believed that only an honest revision of history would enable breaking deeply ingrained historical and national stereotypes which prevent from reaching an agreement. In the discussion, Venclova stresses national and cultural tolerance, which he mostly bases on the idea of cosmopolitanism, referring to its usual meaning of “global citizenship”. Meanwhile, the starting point of Miłosz’s thoughts is the traditions of Grand Duchy of Lithuania. He advocates the conception of a tolerant multi-national and multi-cultural society which is similar to the idea of a civil society.